Body image, weight discrepancy and physical activity in Costa Rican college-students - Chacón Araya, Yamileth (2008)
Purpose: The aim of the study was to describe the body image, perceived and actual body weight and height, and physical activity in Costa Rican college students. Methods: Participants were 126 students (44 males, 82 females) registered for summer school at the Universidad de Costa Rica, in San Jose, Costa Rica. Participants estimated their actual and desired body height and weight, and researchers measured their body height and weight. Body image was determined by visual scales where higher scores represent heavier bodies, and physical activity was determined by the short-version of the International Physical Activity Questionnaire (IPAQ), together with a stages of change questionnaire. Results: Independent samples t tests indicated that males rated themselves differently than females in both, actual and desired body image (p<0.01). Females consistently indicated higher scores in their actual body image (3.21±1.14) than desired body image (2.65±0.64) (p<0.05). No differences were found between actual (3.77±1.21) and desired (3.51±0.67) body image among males (p>0.05). Pearson product-moment correlation indicated a significant association between weight discrepancy and actual body weight (r=−0.36, p<0.001). Finally, compared to females, males overestimated their body height (p=0.026). Twenty-three percent of the students were categorized as being sedentary according to the stages of change questionnaire and no differences in weekly energy expenditure were found between males (mean=5561± 6201 MET-min/week) and females (mean=4207±2797 MET-min/week). Conclusion: Costa Rican males and females with lower body weight rated themselves heavier that what they really were. Similarly to studies in Caucasian and Afro-American populations, Costa Rican college females desired a thinner body image; however, Costa Rican males did not, even though they consistently rated themselves taller than what they really were. No associations between weekly physical activity, energy expenditure and body image were found.